Non-contrast enhanced functional lung MRI in children: report on 900 own measurements using matrix-pencil decomposition (MP-) MRI - Streibel, Carmen; Bauman, Grzegorz; Bieri, Oliver; Pusterla, Orso; Stranzinger, Enno; Willers, C. Corin; Curdy, Marion; Casaulta, Carmen; Frauchiger, Bettina Sarah; Korten, Insa; Yammine, Sophie; Salem, Yasmin; et al. (Frontiers in Pediatrics, 2025)
ObjectivesFunctional imaging of the lungs enables a spatially resolved examination of pulmonary ventilation and perfusion. Non-contrast-enhanced (NCE) magnetic resonance imaging (MRI) techniques do not require specialized set-ups (e.g., hyperpolarized gases), but are applicable on standard clinical MRI scanners. Since patients are not exposed to ionizing radiation during the examinations, NCE-MRI is highly attractive for use in pediatrics, especially in children with chronic lung diseases requiring repeated follow-up measurements.Study designWe report on our own experience of more than 900 NCE-MRI measurements in children over seven years using matrix pencil decomposition (MP-)MRI. We present original data, i.e., clinical cases in which MP-MRI helped in clinical decision-making together with valuable practical points.ResultsAt our center, an optimized workflow including a child-friendly setting and automated provision of outcome protocols led to great acceptance of functional NCE-MRI in patients and clinicians. Within this setting, regular MP-MRI measurements were successfully implemented into clinical routine and proved to be very helpful for surveillance and specific clinical decision-making. We present exemplary cases illustrating the potential of NCE-MRI as a diagnostic tool.ConclusionIn this article, we summarize our unique experience of a large number of MP-MRI measurements. We give an overview on our workflow including standardized and automated analysis and reporting. The exemplary cases from different disease groups illustrate its value in the clinical setting. In conclusion, visualizing regional functional deficits and respective underlying pathophysiological nature of lung impairment seems promising for increasing use of NCE-MRI in the future.